Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Judge Sandra Snyder playing Princess Laya, Judge James Ardaiz in robe with formal white wig; Tomar Mason at microphone 5080 E. Kings Canyon Road, Fresno